Perlindungan Hak Anak Pasca Perceraian melalui Kewenangan Ex Officio Hakim dalam Perspektif Best Interest of the Child - Aisyi, Rahazatul; Ramdhani, Riyan; Hadi, Ahmad Maulana (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
Children are the most vulnerable because they do not have the power to determine their own future. Legal protection for children is crucial within the legal framework of a country that plays an important role in guaranteeing children's rights and welfare, especially children who are victims of divorce. Article 41 letter (b) of Law No. 1 of 1974 concerning Marriage and Article 105 letter (c) of the Compilation of Islamic Law stipulate that in the event of divorce, all costs of child maintenance and education are the responsibility of the father. If the petition for divorce does not include a claim for child support, the judge may determine it ex officio based on the instructions of Supreme Court Circular Letter (SEMA) No. 4 of 2016. However, in religious court practice, this regulation has not been consistently applied by judges in divorce cases where children are victims. This study aims to analyze legal protection for children after divorce from the perspective of the best interests of the child in the practice of Religious Courts in Indonesia. The methodology used is juridical-normative through a review of Islamic legal doctrine, legislation, and other positive laws, which will be studied systematically to provide answers to the issues under investigation. The findings indicate that ex officio authority is an essential instrument for fulfilling children’s rights, particularly child support, even when not explicitly requested in the petition. However, the use of this authority must remain proportional to prevent decisions that exceed the scope of the claims. The study shows that judges possess legitimate discretion to safeguard children’s rights, but more detailed guidelines and an enhanced understanding of the best interests of the child principle are needed to ensure consistent application of ex officio authority. In conclusion, optimizing child rights protection after divorce can be achieved when ex officio authority is applied appropriately, proportionally, and with a strong commitment to the child’s best interests.